Implementation of the Problem-Based Learning Model in Teaching of Mathematics about Adding Fractions with Different Denominators in Elementary Schools - Poluakan, Cosmas; Ratulangi, Norita; Wantu, Meidy (International Journal of Information Technology and Education, 2024)
Research has been carried out to find the level of student ability and the level of difficulty of essay questions on fractions, through polytomous data analysis by applying the Rasch model. The research was conducted in the In-Service Professional Teacher Education program, specifically in the Elementary School Teacher Education. The research was conducted at Belang 1 State Elementary School, Southeast Minahasa Regency, North Sulawesi, Indonesia, in grade 6 with a total of 27 students. Experimental research method with one group pretest-posttest design. The experimental treatment is a Problem-Based Learning (PBL) learning model. The test instrument is in the form of an essay with material on adding fractions with different denominators. The instrument was content validated through a video conference forum attended by experts, tutors, and subject teachers. Data was collected through formative pre-tests and post-tests. Scores are processed as polytomy data. Data analysis used the Rasch model with the Ministep 4.3.2 software application. The results of the analysis, as a class group, the pre-test average was 7.0 and the post-test was 77.0. This group's data shows that the use of the Problem-Based Learning (PBL) model in mathematics learning is very effective. Another conclusion is that the Rasch Model can accurately analyze polytomous data and find 1 student who has a high ability exceeding the highest level of test item difficulty in completing the essay test on adding fractions with different denominators. Then the Rasch Model can analyze the level of difficulty of the 5 items of the essay test instrument, it was found that 2 test items had a low level of difficulty. Using the Rasch model, it is consistently detected that adding fractions with different denominators containing the number 7 is categorized as having a high level of difficulty.